2022
DOI: 10.1111/cup.14300
|View full text |Cite
|
Sign up to set email alerts
|

Sebaceous gland atrophy in seborrheic dermatitis of the scalp; a pilot study

Abstract: Background: Sebaceous gland (SG) atrophy is well-documented in scalp lesions of psoriasis and has been considered as an important clue to psoriatic alopecia. However, its specificity for psoriasis has been questioned over the years. We hypothesize that SG atrophy is not specific for psoriasis and looked for its presence in biopsies of seborrheic dermatitis of the scalp. Methods:We conducted a retrospective study of biopsy specimens of clinically suspected and histopathologically proven seborrheic dermatitis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The authors noted significantly smaller sebaceous lobule size in patients with seborrheic dermatitis compared to other, non-psoriatic inflammatory dermatoses. 10 No patients had a reported history of hair loss; however, two of the six cases evaluated in their series also displayed histological findings compatible with AGA. The authors proposed the idea that "psoriatic alopecia" may reflect a reaction pattern that is not solely confined to psoriasis.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…The authors noted significantly smaller sebaceous lobule size in patients with seborrheic dermatitis compared to other, non-psoriatic inflammatory dermatoses. 10 No patients had a reported history of hair loss; however, two of the six cases evaluated in their series also displayed histological findings compatible with AGA. The authors proposed the idea that "psoriatic alopecia" may reflect a reaction pattern that is not solely confined to psoriasis.…”
Section: Discussionmentioning
confidence: 88%
“…4,5,11 Sebaceous gland atrophy has been defined as a decrease in sebaceous gland size coupled with a decrease in lipidized sebocytes. 10 Sebaceous gland atrophy in psoriasis was first described in a study of cutaneous psoriatic plaques from the scalp. 4 The authors suggested that the atrophic process was reversible as basaloid sebaceous epithelium persisted even in extreme stages of sebaceous gland atrophy, and hypothesized sebaceous gland atrophy was attributed to epidermal growth factor or transforming growth factor-α effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 71 , 72 Studies have shown that age-related changes also result in sebaceous gland atrophy and skin diseases such as psoriasis and dermatitis. 73 75 A recent study using comprehensive lipidomic analysis of meibum, sebum, and tears of a patient with abnormal meibomian and sebaceous gland secretions reported altered composition in various lipid classes in meibum, as well as sebum. 76 Changes in the lipid composition of sebum, as well as meibum, could be important in ocular surface disease, because sebaceous gland secretions may also be incorporated into the tear film.…”
Section: Discussionmentioning
confidence: 99%